UNIVERSITY STUDY QUALITY ASSURANCE AT THE FACULTY: ECONOMICS STUDY PROGRAMME EXPERIENCE - Galinienė, Birutė; Martinavičius, Jonas (Acta Paedagogica Vilnensia, 2011)
The purpose of studies is to provide sufficient application fundamentals of theoretical and practical knowledge, cultivate certain future specialist abilities to ensure the preparation level needed at work. Measurements on quality of studies as well as the study quality assurance are commendable and encouraged, such as the strive towards the ideal study process, superb education, good and prestigious studies, etc. The students’ level of knowledge and professional preparation adequacy to the international requirements, conversely, remarks on quality of studies can always be proclaimed.The internal quality of study evaluation and securitization systems implemented or in the process of implementation in the number of Lithuanian higher education institutions or universities, have gained recognition. These systems are based on standard application of ISO 9001 quality management system, main advantage is recognition of management ability for quality of study process in the division.The Quality management system was designed and the process of implementation in the Faculty of Economics proceeded including different aspects. Main consideration is given to the description of quality of studies at Vilnius University Faculty of Economics, assessed by means of abundant students’ survey data.The survey result processing system gives an opportunity to obtain a thorough view of the study process in respect to teaching and subject quality, popularity, discipline, the level of the taught subjects and obtained useful information on relevant study questions.The obtained results for the quality of studies and quality management system utilization in Vilnius University Faculty of Economics are presented in more details, and the perspectives of the process are foreseen.
Keywords: quality of studies; study quality assessment; quality management system; study programme development